PENGARUH TRANSPARANSI DAN AKUNTABILITAS KEUANGAN SEKOLAH TERHADAP MOTIVASI MENGAJAR GURU DI KABUPATEN KEEROM - Juliana Tandililing (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2019)
The purpose of this study was to analyze the effect of transparency and accountability in school finances with teacher teaching motivation. This study was conducted in Keerom Regency, one of the districts in the Indonesia - Papua New Guinea border region. This research is an empirical study that examines the direct relationship of variables. The population numbered 1,129 teachers, with a sample of 200 people. The results of the study explain the variables of transparency and financial accountability together to influence the teaching motivation of teachers. Partial test results show the effect of transparency is significant, but the effect of accountability was not significant.